Quantitative trait loci affecting natural variation in Drosophila longevity. - Geiger-Thornsberry, G.L.; Mackay, T.F. (Mechanisms of Ageing and Development, 2004)
Limited life span and senescence are universal phenomena, controlled by genetic and environmental factors whose interactions both limit life span and generate variation in life span between individuals, populations and species. To understand the genetic architecture of longevity it is necessary to know what loci affect variation in life span, what are the allelic effects at these loci and what molecular polymorphisms define quantitative trait locus (QTL) alleles. Here, we used quantitative complementation tests to determine whether genes that regulate longevity also contribute to naturally occurring variation in Drosophila life span. Inbred strains derived from a natural population were crossed to stocks containing null mutations (m) or deficiencies (Df) uncovering the candidate genes, maintained over a Balancer (Bal) chromosome. We measured the life span of the resulting F(1) genotypes, +(i)/m (Df) and +(i)/Bal, where +(i) denotes one of the i natural alleles. Failure of the QTL alleles to complement the candidate gene mutation is indicated by a significant cross (mutant versus wild-type allele of the candidate gene) by inbred line interaction term from analysis of variance of life span. Failure to complement indicates a genetic interaction between the candidate gene allele and the naturally occurring life span QTL, and implicates the candidate gene as potential cause of variation in longevity. Of the 16 candidate regions and genes tested, Df(2L)c17, Df(3L)Ly, Df(3L)AC1 and Df(3R)e-BS2 showed significant failure to complement wild-type alleles in both sexes, and an Alcohol dehydrogenase mutant failed to complement in females. Several genes that regulate life span (e.g., Superoxide dismutase, Catalase, and rosy) complemented the life span effects of wild-derived alleles, suggesting little natural variation affecting longevity at these loci, at least in this sample of alleles. Quantitative complementation tests are therefore useful for identifying QTL contributing to segregating genetic variation in life span in nature.